Beyond the Pulpit and the Screen: Digital Fatwas and the Transformation of Islamic Legal Authority in Nigeria - Abdulkabeer Akinlabi Habeebullah; Aysel Aliyeva; Haoua Zeinabou; Fonkoua Moussa Abdoulaye; Leyla Heikkinen (Indonesian Journal of Islamic Law, 2026)
The rapid expansion of digital media has significantly altered the circulation of religious authority, raising new questions about how Islamic legal interpretation operates beyond traditional scholarly institutions. This article investigates how digital fatwas reshape the production and legitimacy of Islamic legal authority in Nigeria, a context where Islamic jurisprudence interacts with diverse social, institutional, and technological environments. The study positions digital fatwas not merely as new channels of dissemination but as socio-legal arenas in which authority is negotiated among scholars, digital platforms, and religious audiences. Drawing on qualitative socio-legal methods, including discourse analysis of online fatwas, platform observation, and interviews with scholars and digital religious actors, the article examines how Islamic legal opinions circulate and gain legitimacy within contemporary digital ecosystems. The findings demonstrate that digitalisation does not eliminate traditional scholarly authority; rather, it reconfigures it into a relational and networked form in which credibility is co-produced through scholarly reputation, technological mediation, and audience engagement. By analysing the transformation of fatwa practices in Nigeria, the article contributes to broader debates on Islamic law as a discursive and institutional phenomenon. It shows how emerging digital infrastructures reshape the dynamics of ijtihād, authority, and legal interpretation in the Global South, offering new insights into how Islamic legal authority adapts to evolving socio-technological contexts.